VCO (Vinegar Cleaner Organic) Based with Orange's peel, Cinnamon, and Rosemary Extract - Ahsani, Aulia Maqdum; Putri Afifah Augusta; Lovely Emeralda; Pasha Nur Azizah; Aulia Ayu Azahra; Susanti Rahayu (Jurnal Integrasi Sains dan Quran, 2023)
Orange peel is an organic waste that contains vitamin C, essential oils and pectin. The essential oil content in orange peel and cinnamon waste can ward off ants and can be used as a versatile cleaning liquid with white vinegar as a solvent. The purpose of this study was to determine the characteristics of cleaning fluids based on orange peel waste, white vinegar, cinnamon, and rosemary leaves as cleaning liquids that can ward off ants and find out their impact on the surrounding environment. The results obtained in the organoleptic color test in the form of 7 out of 10 respondents chose a brownish-yellow color, there was an organoleptic aroma test in the form of 10 respondents judged that at a distance of 25 cm the aroma was still strongly smelled, there is a test of effectiveness as a cleaning fluid, 10 respondents rated it very clean. Also on the test of effectiveness as an ant’s repellents fluid, 10 respondents rated ants away at a range of time from 1-5 minutes. It can be concluded that VCO is a versatile cleaning fluid made from natural ingredients and can ward off ants.